Association of left atrial low-voltage area and thromboembolic risk in patients with atrial fibrillation. Issue Volume 20:Issue FI 3(2018) (25th July 2017) - Müller, Patrick; Makimoto, Hisaki; Dietrich, Johannes W; Fochler, Franzsika; Nentwich, Karin; Krug, Joachum; Duncker, David; Blockhaus, Christian; Kelm, Malte; Fürnkranz, Alexander; Deneke, Thomas; Halbfass, Philipp
Abstract: Aims: Atrial fibrillation (AF) is associated with thromboembolic events. Currently, the CHA2DS2-VASc score is recommended for thromboembolic risk stratification in non-valvular AF patients. However, recent data suggested a potential role of atrial remodelling on thromboembolism. This study aimed to assess the association between left atrial low-voltage area (LVA) and history of clinical manifest as well as subclinical silent cerebral ischaemia (SCI) in AF patients. Methods and results: Two-hundred patients [64 ± 10.5 years, 75 women (37.5%)] with symptomatic paroxysmal ( n = 88, 44%) or persistent AF undergoing pulmonary vein isolation (PVI) were prospectively enrolled. Left atrial LVA (bipolar voltage < 0.5mV) was evaluated by intra-procedural mapping (>300 points per patient) during sinus rhythm. Cerebral delayed-enhancement magnetic resonance imaging was performed after PVI for detection of pre-existing procedural-independent SCI. Over all, 17 patients (8.5%) had previous history of stroke. Pre-existing SCIs were detected in 135 patients (67.5%). Patients with previous stroke (4.0 ± 1.5 vs. 2.1 ± 1.3, P < 0.0001) and pre-existing SCI (2.7 ± 1.3 vs. 1.5 ± 1.4, P < 0.0001) had a significantly higher CHA2DS2-VASc score. LVA was significantly larger in patients with previous stroke (12.5 ± 8.5% vs. 3.4 ± 5.4%, P < 0.0001) as well as pre-existing SCI (5.8 ± 6.9% vs. 0.8 ± 1.7%, P < 0.0001). Multivariate regression analysis revealed that LVA was independently associated with the presence of SCI [hazard ratio (HR) per 1% LVA 1.13 (1.06–1.22), P = 0.0003] and history of stroke [HR per 1% LVA 1.36 (1.19–1.60), P < 0.0001] after adjustment of CHA2 DS2 -VASc score. Conclusion: Left atrial LVA is associated with history of stroke and SCI in patients with non-valvular AF and might improve thromboembolic risk stratification after confirmation of its predictive value in future studies.